KURANGNYA DUKUNGAN SUAMI, RIWAYAT ANEMIA DAN KEK SEBAGAI FAKTOR RISIKO KEGAGALAN ASI EKSKLUSIF - Firdananda Fikri Jauharany; Ardelita Ika Fadhlillah; Agus Sartono (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2023)
ABSTRACT Background: The government and various health organizations have recommended and campaigned for the importance of exclusive breastfeeding. However, exclusive breastfeeding is still relatively low to this day. Various factors influencing exclusive breastfeeding include the husband's support, maternal health, and nutritional status.Objectives: This study aims to analyze the history of anemia, history of CED (Chronic Energy Deficiency), and husband's support as risk factors for failure of exclusive breastfeeding.Methods: An analytic study of 60 breastfeeding mothers was conducted to analyze the factors of husband support, history of anemia and CED during pregnancy as risk factors for failure of exclusive breastfeeding. The husband's support and exclusive breastfeeding status were measured through interviews using a questionnaire. A history of anemia and CED can be identified by looking at the records of hemoglobin levels and MUAC (mid-upper arm circumference) in the Maternal and Child Health Book. Data analysis used the Chi-Square and Odd-Ratio tests.Results: The chi-square test showed a significant relationship between the husband's support and the success of exclusive breastfeeding (p<0.001). There was no relationship between the history of CED (p=0.315) and anemia (0.219) with exclusive breastfeeding status. Breastfeeding mothers whose husbands do not support to practice of exclusive breastfeeding are 8.636 times more likely to experience failure in exclusive breastfeeding.Conclusion: Lack of husband support is a risk factor for failure of exclusive breastfeeding.Keywords: Anemia; Chronic energy deficiency; Exclusive breastfeeding; Husband support; ABSTRAK Latar belakang: Pemerintah dan berbagai organisasi kesehatan telah merekomendasikan dan mengkampanyekan pentingnya pemberian ASI eksklusif. Namun, pemberian ASI eksklusif masih tergolong rendah sampai hari ini. Berbagai faktor yang mempengaruhi pemberian ASI eksklusif antara lain dukungan suami, kesehatan ibu dan status gizi.Tujuan: penelitian ini bertujuan untuk mengkaji riwayat anemia, riwayat KEK (Kekurangan Energi Kronis), dan dukungan suami sebagai faktor risiko kegagalan ASI eksklusif.Metode: Sebuah studi analitik dengan desain kasus kontrol pada 60 ibu menyusui dilakukan untuk mengkaji faktor dukungan suami, riwayat anemia dan KEK selama kehamilan sebagai faktor risiko kegagalan pemberian ASI eksklusif. Dukungan suami dan status ASI eksklusif diukur melalui wawancara dengan menggunakan kuesioner. Riwayat anemia dan KEK dapat diketahui dengan melihat catatan kadar hemoglobin dan LiLA (Lingkar Lengan Atas) pada Buku Kesehatan Ibu dan Anak. Analisis data menggunakan uji Chi-Square dan Odd-Ratio.Hasil: Uji chi-square menunjukkan adanya hubungan yang bermakna antara dukungan suami dengan keberhasilan pemberian ASI eksklusif (p<0,001). Tidak ada hubungan antara riwayat KEK (p=0,315) dan anemia (0,219) dengan status pemberian ASI eksklusif. Ibu menyusui yang tidak didukung suami untuk mempraktikkan ASI eksklusif berisiko 8,636 kali lebih besar mengalami kegagalan dalam memberikan ASI eksklusif.Simpulan: Kurangnya dukungan suami merupakan salah satu faktor risiko kegagalan pemberian ASI eksklusif.Kata Kunci : Anemia; ASI eksklusif; Dukungan suami; Kekurangan energi kronis